Biological membrane base material, preparation method and application

A biomembrane substrate was prepared by using a crosslinking network of k-type wrinkled carrageenan, l-type red algae gum, and eggshell membrane powder. This solved the problem of balancing the mechanical strength and transdermal efficiency of natural membrane materials, achieving a balance between high mechanical strength, transdermal efficiency, and biocompatibility.

CN121360261APending Publication Date: 2026-01-20PHARMA CO LTD TIANJIN HEZHIYOUDE
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202511947517.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-12-23
Publication Date
2026-01-20

AI Technical Summary

Technical Problem

Existing natural membrane materials struggle to balance mechanical strength and transdermal efficiency; traditional plastic films are difficult to degrade; synthetic polymer membranes have poor biocompatibility; cosmetic masks have low transdermal absorption rates; and medical dressings struggle to balance breathability and anti-adhesion.

Method used

A biomembrane substrate was prepared by combining k-type wrinkled carrageenan, l-type red algae gum, and eggshell membrane powder, forming a three-dimensional network through metal ion cross-linking, and then combining the fiber reinforcement of eggshell membrane powder.

Benefits of technology

It achieves high mechanical strength, increases transdermal penetration to 22-28%, and precisely controls swelling rate at 80-100%. It also balances biocompatibility and biodegradability, making it suitable for medical dressings and cosmetic masks.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_6
    Figure SMS_6
  • Figure SMS_7
    Figure SMS_7
Patent Text Reader

Abstract

The invention provides a biological membrane base material, a preparation method and application, and relates to the technical field of biological materials. The biological membrane base material is prepared by mixing and cross-linking carrageenan, red algae glue, eggshell membrane powder and glycerol and carrying out post-treatment on the carrageenan, the red algae glue, the eggshell membrane powder and the glycerol. The tear resistance is greater than 40N / mm < 2 >, and the requirements of medical dressing are met; the transdermal absorption rate of the active ingredients is increased to 20% or above; the raw materials are all natural components, are non-irritant and can be completely degraded in the natural environment or in the body, and the pollution problem of a traditional plastic film is solved.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application relates to the technical field of biomaterial technology, and particularly relates to a biomembrane substrate, a preparation method and application. BACKGROUND

[0002] In the cross field of material science and biomedical, cosmetics, etc., the performance requirement of membrane material is strict. Traditional plastic film is difficult to degrade, causing environmental pollution; some synthetic polymer films have poor biocompatibility, easily causing adverse reactions, limiting their application in medical dressings, cosmetic masks and other scenes.

[0003] Natural polysaccharide films are concerned due to their biocompatibility and degradability, such as chitosan film and cellulose film, which have certain application potential, but the single film has insufficient mechanical properties, is easy to swell and disintegrate in a wet environment, and has low utilization rate of active ingredients in cosmetic applications.

[0004] Medical dressings need to have both air permeability and anti-adhesion, and existing products are difficult to balance; the transdermal absorption rate of cosmetic masks is generally less than 15%, and some added chemical cross-linking agents may irritate the skin.

[0005] In summary, it is a key problem to be solved to develop a natural-based composite film material with good biocompatibility, degradability, suitable mechanical strength and high transdermal absorption efficiency of active ingredients. SUMMARY

[0006] In order to solve the above-mentioned defects and deficiencies in the prior art, the present application aims to provide a biomembrane substrate, a preparation method and application.

[0007] One of the purposes of the present application is to provide a biomembrane substrate, the raw materials of the biomembrane substrate including k-type chondrus crispus gel, l-type furcellaran, eggshell membrane powder, glycerol and metal ion cross-linking agent; The k-type chondrus crispus gel has a gel strength of 800-1200 g / cm 2 , and a purity of ≥90%; The l-type furcellaran has a viscosity of 300-500 mPa s, and a G unit content of 60%-85%; The mass ratio of the k-type chondrus crispus gel, the l-type furcellaran and the eggshell membrane powder is 9-12:4-6:1-2.

[0008] Preferably, the k-type chondrus crispus gel includes one or more of Satiagel™ UTH 18, Genugel® X-902-02 or KELCO® K-CARRA 100; The l-type furcellaran includes one or more of Genu Gum® I-160, Alginure® I-03 or DH-I-05.

[0009] The second object of the present application is to provide a preparation method of the biomembrane substrate as described above, characterized in that it comprises the following steps: The k-type carrageenan and the l-type furcellaran are uniformly dispersed in glycerol with the eggshell membrane powder, an aqueous dispersion medium is added and stirred, and then a metal ion crosslinking agent is added, and the mixture is blended at 80-90 DEG C for 20-60 min to obtain a mixed sol solution; The mixed sol solution is cooled to 50-60 DEG C, the functional substance is added, and defoaming is performed at constant temperature for 30-50 min; After adjusting the thickness, casting is performed, and low-temperature drying, cutting and sealing packaging are performed to obtain the biomembrane substrate.

[0010] Preferably, the aqueous dispersion medium is added in an amount of 65-88.6% of the total mass of the mixed sol solution.

[0011] Preferably, the aqueous dispersion medium comprises a phosphate buffer and / or pure water. The pH value of the phosphate buffer is 6.8-7.2.

[0012] Preferably, the metal ion crosslinking agent comprises Ca 2+ And / or Al 3+ .

[0013] The third object of the present application is to provide an application of the biomembrane substrate as described above in the field of medical dressings, wherein the medical dressing comprises a wound dressing or a burn dressing.

[0014] The fourth object of the present application is to provide an application of the biomembrane substrate as described above in the field of cosmetics, wherein the biomembrane substrate is used for preparing a mask and / or a skin care essence carrier.

[0015] The present application has the following beneficial effects: The present application forms a structural and functional dual synergistic system by using the eggshell membrane powder, the k-type carrageenan and the l-type furcellaran, and a biomembrane substrate is prepared, thereby solving the problem that the mechanical strength and the transdermal efficiency of the existing natural membrane material are difficult to be considered.

[0016] The double alginates are crosslinked by metal ions to form a basic three-dimensional network, and the I / V type collagen fibers and protein molecules in the eggshell membrane powder are embedded in the network, which not only fills the gaps in the double alginates network and improves the crosslinking density, but also relieves the brittleness of the pure polysaccharide membrane, so that the tear resistance of the membrane material is stable at >40 N / mm 2 , the wet strength of the dry membrane is 11-15 MPa, and the swelling rate is accurately controlled at 80-100%, thereby solving the defects that the traditional natural membrane material is easy to swell and disintegrate in the exudate of the wound surface and the wet environment of the skin.

[0017] The eggshell membrane powder is highly homologous to human skin tissue, and the protein molecules form a biological affinity layer at the membrane material-skin interface, which reduces the skin barrier resistance; the affinity layer cooperates with the double alginate gel network, so that the active ingredients can not only be released slowly through the double alginate gel, but also penetrate rapidly with the aid of the affinity of the eggshell membrane powder, and finally the transdermal rate is increased to 22-28%, which is much higher than that of the existing natural membrane materials.

[0018] The eggshell membrane powder and the double alginate gel are both natural ingredients, and can be completely degraded in a natural environment or in vivo, and have both biocompatibility and environmental protection value.

[0019] In summary, the eggshell membrane powder realizes the triple balance of high mechanical strength, high transdermal rate and high safety through structural embedding, transdermal assistance and functional complementation with the double alginate gel. DETAILED DESCRIPTION

[0020] According to a first aspect of the present application, a biological membrane base material is provided, and raw materials of the biological membrane base material include k-type corrugated carrageenan, l-type red algae gel, eggshell membrane powder, glycerol and metal ion crosslinking agent; The k-type corrugated carrageenan has a gel strength of 800-1200 g / cm 2 , and a purity of ≥90%; The l-type red algae gel has a viscosity of 300-500 mPa s, and a G unit content of 60%-85%; The mass ratio of the k-type corrugated carrageenan, the l-type red algae gel and the eggshell membrane powder is 9-12:4-6:1-2. In the present application, the k-type corrugated carrageenan contains sulfate groups and carboxyl groups, the l-type red algae gel contains 3,6-endothiol-L-galactose and carboxyl groups, and the carboxyl groups and hydroxyl groups of the two can coordinate with Ca 2+ , Al 3+ , so that the linear molecular chains are crosslinked into a three-dimensional network. The network can limit the movement of the molecular chains, improve the tear resistance, hinder the penetration of water molecules, reduce the swelling rate, and combine with the fiber enhancement of the eggshell membrane powder, and finally realize high performance.

[0021] The k-type corrugated carrageenan is the mechanical skeleton core of the membrane material, and the k-type carrageenan unit (1,3-β-D-galactose-4-sulfate / 1,4-α-D-galactose) in the molecule needs to form an egg box type crosslinked network with metal ions. 800 g / cm 2 is the lower limit of the strength, and below this value, the crosslinked network is sparse, and the wet state of the membrane material is easy to disintegrate; 1200 g / cm 2For the upper limit of strength, above this value, the brittleness of the adhesive itself increases, and after mixing with l-type red algae glue, phase separation is easy to occur, resulting in fluctuation of film tear resistance. This range can ensure that the wet strength of the dry film is stable at 11-15 MPa, meeting the needs of wound / burn dressing to resist the immersion of exudate. High purity can avoid impurities interfering with cross-linking reaction, if the purity is <90%, impurities will occupy metal ion cross-linking sites, resulting in a decrease in cross-linking density, weakening the mechanical strength of the film. At the same time, high purity can reduce the risk of skin irritation.

[0022] Viscosity is directly related to the dispersibility of raw materials and the synergistic effect of cross-linking, below 300 mPa s, l-type red algae glue and k-type chondrus crispus glue are easy to separate when mixed, and cannot form a uniform cross-linked network, resulting in large local tear resistance difference of the film; above 500 mPa s, the flowability of the mixed sol solution is too poor, the thickness is difficult to control during casting film formation, and cracks are easy to occur after drying. This viscosity range can ensure uniform dispersion of the sol solution, form a continuous film material with subsequent process, and at the same time, adjust the swelling rate to 80-100% through hydrophilicity to avoid excessive swelling or insufficient swelling. G unit (1,4-beta-D-glucuronic acid) is the cross-linking active core of l-type red algae glue, when the content of G unit is below 60%, the coordination cross-linking site of G unit and Al 3+ is insufficient, the basic network of k-type glue cannot be strengthened, the tear resistance of the film is easy to be <40 N / mm 2 , and the hydrophilicity decreases, increasing the resistance of active ingredients to transdermal penetration; when the content of G unit is higher than 85%, the hydrogen bond interaction between the molecular chains is too strong, which will cause the viscosity of the sol solution to exceed 500 mPa s upper limit, and excessive cross-linking increases the brittleness of the film, and at the same time, the swelling rate is <80%, the skin adhesion is poor. This range can balance the cross-linking activity and performance, helping to improve the transdermal rate to 22-28%.

[0023] K-type chondrus crispus glue as a mechanical skeleton, below 9 parts, the basic cross-linked network is incomplete, the tear resistance is <40 N / mm 2 , and the wet strength of the dry film is <11 MPa; above 12 parts, the film is easy to be brittle due to too high proportion of k-type glue, and the elongation at break decreases. This proportion can ensure that the mechanical properties of the film meet the standards, and at the same time, reserve functional space for other components. When l-type red algae glue is below 4 parts, the cross-linking synergy is insufficient, the swelling rate is easy to be >100%, and the film is easy to deform in a wet environment; 6 parts is the upper limit, above 6 parts, excessive hydrophilicity leads to a swelling rate >100%, and may compete with k-type glue for metal ion cross-linking sites, which in turn weakens the mechanical strength. This proportion can precisely control the swelling rate to 80-100%, and at the same time, strengthen the cross-linked network, and assist in improving the transdermal efficiency.

[0024] When the eggshell membrane powder is less than 1 part, the effect of the rich protein and the type I / type V collagen fibers will be significantly weakened: on the one hand, the affinity of the membrane material to the skin is reduced, and wrinkles, peeling and other problems are prone to occur when the skin is attached, especially in the long-term attachment scenario of cosmetic masks or medical dressings, the use experience and attachment stability are greatly reduced; on the other hand, the active ingredient penetration assistance is insufficient, even if the double algal glue cross-linking network can guarantee the basic transdermal channel, it is difficult to further improve the penetration efficiency of the active ingredient, and the transdermal rate is prone to fall below 20%, which cannot achieve the core index of high transdermal rate.

[0025] At the same time, the nutritional support required for wound repair in a medical scenario will be significantly insufficient, and the moisturizing and repairing effects in cosmetic applications will also be weakened; and the complementary effect of the double algal glue cross-linking network is missing, the membrane material can still maintain the basic mechanical strength, but the overall performance balance is reduced, such as the skin stability in a wet environment, the mild repair effect after long-term use, etc. Details will have short boards, and it is difficult to achieve the synergistic effect of high mechanical strength-high transdermal rate-optimal repair.

[0026] In a preferred embodiment of the present application, the k-type carrageenan includes one or more of Satiagel™ UTH 18, Genugel® X-902-02 or KELCO® K-CARRA 100; the l-type furcellaran includes one or more of Genu Gum® I-160, Alginure® I-03 or DH-I-05.

[0027] According to a second aspect of the present application, a preparation method of the biological membrane substrate is provided, and has the characteristics that it comprises the following steps: The wrinkle carrageenan, furcellaran and the eggshell membrane powder are uniformly dispersed in glycerol, an aqueous dispersion medium is added and stirred, then a metal ion crosslinking agent is added, the temperature is raised to 80-90°C, and the mixture is blended for 20-60 min to obtain a mixed sol solution; The mixed sol solution is cooled to 50-60°C, the active ingredient is added, and defoaming is performed at constant temperature for 30-50 min; After adjusting the thickness, casting is performed, low-temperature drying, cutting and sealing packaging are performed, and the biological membrane substrate is prepared.

[0028] In a preferred embodiment of the present application, the addition amount of the glycerol is 5-10% of the total mass of the mixed sol solution.

[0029] In a preferred embodiment of the present application, the addition amount of the aqueous dispersion medium is 65-88.6% of the total mass of the mixed sol solution.

[0030] The adding amount of the aqueous dispersion medium is set to 65-88.6% of the total mass of the mixed sol solution, which is based on the requirements of raw material dispersibility, film forming process stability and film material performance regulation. In the preparation process, the wrinkle chondrus gel, red algae gel and eggshell membrane powder are dispersed in glycerol, and then the aqueous dispersion medium is added and mixed and stirred. The lower limit of 65% can ensure that the high molecular colloid is fully swollen and a uniform system is formed, avoiding the agglomeration of raw materials due to insufficient liquid amount, which affects the uniformity of the subsequent crosslinking reaction; if the adding amount is < 65%, the mixed liquid is easy to be a viscous paste, which cannot form a stable sol, and then leads to the local mechanical property difference of the film material.

[0031] The crosslinking stage needs a suitable liquid environment to ensure that the reaction is fully carried out, and the upper limit of 88.6% can avoid the mixed sol solution being too dilute, so as to ensure that the gel-like material with certain viscosity is formed after crosslinking, which meets the controllability of the thickness of the casting film; if the adding amount is > 88.6%, the sol solution has too strong fluidity, it is difficult to maintain the preset thickness during casting, and the film material is easy to shrink too much during the drying process due to too much water.

[0032] The content of the aqueous dispersion medium directly affects the compactness of the film material after drying. The adding amount of 65-88.6% can make the film material form a three-dimensional crosslinking network with moderate density after low-temperature drying: on the one hand, this content can ensure that the water is slowly and uniformly volatilized during the drying process, avoiding the agglomeration of colloid molecules due to too little water, which forms a hard and brittle film with too high density. Such a hard and brittle film will hinder the penetration of active ingredients, and also reduce the skin flexibility, which cannot meet the needs of medical dressings adhering to the wound and cosmetic masks adhering to the facial contour; on the other hand, it can also avoid the film material shrinkage exceeding the standard after drying due to too much water, which causes cracks or local pore unevenness, destroys the continuity of the crosslinking network constructed by the double algae gel and metal ions, and then weakens the tear resistance and wet stability of the film material.

[0033] The moderate compact structure formed finally can not only retain reasonable intermolecular gaps to ensure the air and moisture permeability, but also provide efficient channels for the penetration of active ingredients, cooperate with the skin affinity of the eggshell membrane powder, and help to stabilize the transdermal rate at 22-28%; at the same time, the uniform crosslinking network can also accurately regulate the swelling rate to 80-100%, avoiding the film material from excessive swelling and disintegration in a wet environment or insufficient swelling leading to poor adhesion, which completely meets the core performance requirements of medical wound / burn dressings and cosmetic masks, and does not affect the natural degradable properties of the raw materials.

[0034] In the present application, the efficacy material refers to the core active ingredient added to the mixed sol solution in the preparation process to realize the specific application function of the biological film base material. It needs to be compatible with the natural ingredients and crosslinking system of the biological film base material, does not destroy the mechanical properties, biocompatibility and degradability of the base material, and at the same time can efficiently exert the target efficacy with the help of the high transdermal rate and skin adhesion of the base material.

[0035] The specific application function is, for example, antibacterial, wound repair in medical scenarios, moisturizing, antioxidant and other functions in cosmetic scenarios.

[0036] In the present application, the efficacy substance is, for example, an antibacterial peptide, a silk protein, a biological fermentation liquor or caffeine and a complex thereof.

[0037] In a preferred embodiment of the present application, the aqueous dispersion medium comprises a phosphate buffer and / or pure water; the pH value of the phosphate buffer is 6.8-7.2.

[0038] In the present application, the molecular structure stability of natural polysaccharide components such as wrinkle carrageenan and red algae gum is greatly affected by pH value. The weakly acidic to neutral range of 6.8-7.2 can avoid the polysaccharide chain breakage caused by excessively strong acidity (pH < 6.8) or the excessive aggregation between gum molecules caused by excessively strong alkalinity (pH > 7.2), ensuring that the double-algae gum can normally swell and participate in the subsequent crosslinking reaction, laying a foundation for forming a stable three-dimensional network structure.

[0039] Metal ions (Ca 2+ , Al 3+ ) are added for crosslinking, and the pH environment of 6.8-7.2 provides suitable conditions for the reaction. Metal ions are not prone to hydrolysis and precipitation in this pH range, can stably combine with active groups in the double-algae gum, form a dense ionic crosslinking network, and ensure that the film material meets the standards for tear resistance (> 40 N / mm²) and wet strength.

[0040] When the film material is applied to medical dressings and cosmetic mask scenarios, it needs to have good adaptability to the human physiological environment. The phosphate buffer with a pH of 6.8-7.2 can adjust the pH of the mixed system to a physiologically friendly range, avoid causing skin irritation, inflammatory reactions, or affecting the wound healing process due to excessively high or low pH, and meet the core requirement of biocompatibility.

[0041] In a preferred embodiment of the present application, the metal ion crosslinking agent comprises Ca 2+ , Al 3+ .

[0042] In the present application, the molecular structure of wrinkle carrageenan and red algae gum contains a large number of active groups such as carboxyl and hydroxyl groups, and Ca 2+ , Al 3+ can combine with these groups through coordination bonds to form a stable three-dimensional crosslinking network. Among them, Ca 2+ , as a divalent ion, can form an egg-box type crosslinking structure with gum molecules to provide basic mechanical strength for the film material; Al 3+As a trivalent ion, the cross-linking site is more, which can enhance the network density, further improve the tear resistance (> 40N / mm2) and wet stability of the film material, and avoid the problem that the single natural polysaccharide film is easy to swell and disintegrate in a wet environment.

[0043] Ca 2+ , Al 3+ are biocompatible metal ions, and can participate in normal metabolism in a physiological environment. Ca 2+ is an essential element for the human body, participates in bone formation and cell signal transduction, and the residual amount thereof in the film material will not cause an immune response or skin irritation, which is suitable for medical dressing and cosmetic mask scenarios; Al 3+ has good biocompatibility at a low concentration, and can avoid toxicity risk by adjusting the addition amount, and at the same time, the strong cross-linking ability can prolong the sustained-release period (> 7 days) of the active ingredients of the drug or cosmetic.

[0044] The cross-linking degree of Ca 2+ , Al 3+ can be adjusted by the concentration to avoid the densification of the film material caused by excessive cross-linking.

[0045] In summary, Ca 2+ , Al 3+ as a cross-linking agent can not only ensure the mechanical properties and stability of the film material through efficient cross-linking, but also can balance the biocompatibility and functional properties, and is highly compatible with the tear resistance, high skin permeability and degradable core advantages of the film material.

[0046] According to a third aspect of the present application, the application provides a use of the biological film substrate as described above in the field of medical dressings, wherein the medical dressing comprises a wound dressing or a burn dressing.

[0047] In the present application, when the biological film substrate is used for a wound dressing, the biological film substrate can load an antibiotic-metal nanocomposite, which promotes wound tissue regeneration, inhibits bacterial infection, and can be naturally degraded after wound healing, avoiding secondary damage, by virtue of good biocompatibility, tear resistance (> 40N / mm 2 ) and air and moisture permeability. When the biological film substrate is used for a burn dressing, it has a wet strength of ≥10MPa, can withstand the exudate environment of a burn wound surface without disintegration, and at the same time, through the action of type I / type V collagen in eggshell membrane powder, the repair process of the burn wound surface is accelerated, and the formation of scars is reduced.

[0048] According to a fourth aspect of the present application, the application provides a use of the biological film substrate as described above in the field of cosmetics, wherein the biological film substrate is used for preparing a mask and / or a skin care essence carrier.

[0049] In the present application, when the biofilm substrate is used to prepare a facial mask, the biofilm substrate can load cosmetic active ingredients such as liposome-encapsulated peptides, caffeine and its complexes, silk proteins, and bio-fermentation liquor, has good skin adhesion, and can be naturally degraded after use; when the biofilm substrate is used to prepare a skin care serum carrier, the good biocompatibility can avoid skin irritation, the structure formed by compounding the diatomaceous gel and eggshell membrane powder can stably carry the serum ingredients and control the release rate, enhance the moisturizing and antioxidant effects of the skin care serum, and the degradable property reduces the environmental burden.

[0050] The present application will be further described in detail below with reference to examples. The specific examples described herein are only used to explain the related application, and are not a limitation on the application. The examples in the present application and the features in the examples can be combined with each other without conflict. The present application will be described in detail below with reference to examples.

[0051] Example 1 0.9 parts of k-type chondrus crispus gel (Genugel® X-902-02), 0.4 parts of l-type furcellaran (Genu Gum® I-160), and 0.1 parts of eggshell membrane powder were uniformly dispersed in 7 parts of glycerol, 85 parts of an aqueous dispersion medium (phosphate buffer, pH = 7.0) was added, mixed and stirred, and then 0.2 parts of Ca 2+ The crosslinking agent (calcium chloride) was blended at 85°C for 40 min to obtain a mixed sol solution; The mixed sol solution was cooled to 55°C, 0.2 parts of an antibacterial peptide was added, and defoaming was performed at constant temperature for 40 min; After adjusting the thickness to 0.1 mm, casting was performed, low-temperature drying was performed at 40°C, cutting was performed, and sealing and packaging were performed to obtain the biofilm substrate.

[0052] Example 2 1.0 parts of k-type chondrus crispus gel (Genugel® X-902-02), 0.5 parts of l-type furcellaran (Genu Gum® I-160), and 0.15 parts of eggshell membrane powder were uniformly dispersed in 6 parts of glycerol, 86 parts of an aqueous dispersion medium (pure water) was added, mixed and stirred, and then 0.3 parts of Al 3+ The crosslinking agent (aluminum glycoside) was blended at 80°C for 60 min to obtain a mixed sol solution; The mixed sol solution was cooled to 50°C, 4.5 parts of an antibacterial peptide was added, and defoaming was performed at constant temperature for 30 min; After adjusting the thickness to 0.12 mm, casting was performed, low-temperature drying was performed at 35°C, cutting was performed, and sealing and packaging were performed to obtain the biofilm substrate.

[0053] Example 3 K-CARRA 100, 0.4 parts of l-type furcellaran (Alginure® I-03) and 0.2 parts of eggshell membrane powder were uniformly dispersed in 9.5 parts of glycerol, 88.6 parts of an aqueous dispersion medium (phosphate buffer + pure water, volume ratio 1:1, pH = 6.8) was added and stirred, and then 0.1 parts of Ca 2+ / Al 3+ The crosslinking agent (calcium chloride and glycoxy aluminum, mass ratio 1:1) was mixed and blended at 90°C for 20 min to obtain a mixed sol solution; The mixed sol solution was cooled to 60°C, 6 parts of antibacterial peptide was added, and defoaming was carried out at constant temperature for 50 min; After adjusting the thickness to 0.08 mm, casting was carried out, low-temperature drying at 45°C, cutting type, sealing and packaging to obtain a biological membrane substrate.

[0054] Example 4 0.95 parts of k-type wrinkle carrageenan (Satiagel™ UTH 18), 0.45 parts of l-type furcellaran (Alginure® I-03) and 0.12 parts of eggshell membrane powder were uniformly dispersed in 5 parts of glycerol, 78 parts of an aqueous dispersion medium (phosphate buffer, pH = 7.2) was added and stirred, and then 0.23 parts of Ca 2+ crosslinking agent was added, and the temperature was raised to 82°C for 50 min to obtain a mixed sol solution; The mixed sol solution was cooled to 52°C, 4.5 parts of antibacterial peptide was added, and defoaming was carried out at constant temperature for 35 min; After adjusting the thickness to 0.15 mm, casting was carried out, low-temperature drying at 38°C, cutting type, sealing and packaging to obtain a biological membrane substrate.

[0055] Example 5 1.1 parts of k-type wrinkle carrageenan (Genugel® X-902-02), 0.55 parts of l-type furcellaran (Genu Gum® I-160) and 0.18 parts of eggshell membrane powder were uniformly dispersed in 8 parts of glycerol, 72 parts of an aqueous dispersion medium (pure water) was added and stirred, and then 0.22 parts of Al 3+ crosslinking agent was added, and the temperature was raised to 88°C for 30 min to obtain a mixed sol solution; The mixed sol solution was cooled to 58°C, 3.5 parts of antibacterial peptide was added, and defoaming was carried out at constant temperature for 45 min; After adjusting the thickness to 0.1 mm, casting was carried out, low-temperature drying at 42°C, cutting type, sealing and packaging to obtain a biological membrane substrate.

[0056] Example 6 1.05 parts of k-type carrageenan (Genugel® X-902-02), 0.48 parts of l-type furcellaran (DH-I-05) and 0.13 parts of eggshell membrane powder were uniformly dispersed in 7.5 parts of glycerol, 73 parts of an aqueous dispersion medium (phosphate buffer + pure water, volume ratio 2:1, pH = 7.0) was added and stirred, and then 0.25 parts of Ca 2+ / Al 3+ The crosslinking agents were mixed (mass ratio 2:1), and the temperature was raised to 86°C for 35 min to obtain a mixed sol solution; The mixed sol solution was cooled to 54°C, 3.4 parts of antibacterial peptide was added, and defoaming was performed at constant temperature for 40 min; After adjusting the thickness to 0.13 mm, casting was performed, and the biological membrane substrate was obtained after low-temperature drying at 36°C, cutting, and sealing packaging.

[0057] Example 7 0.9 parts of k-type carrageenan (KELCO® K-CARRA 100), 0.6 parts of l-type furcellaran (Alginure® I-03) and 0.2 parts of eggshell membrane powder were uniformly dispersed in 9 parts of glycerol, 65 parts of an aqueous dispersion medium (phosphate buffer, pH = 6.9) was added and stirred, and then 0.3 parts of Ca 2+ crosslinking agent was added, the temperature was raised to 84°C for 45 min to obtain a mixed sol solution; The mixed sol solution was cooled to 56°C, 5 parts of antibacterial peptide was added, and defoaming was performed at constant temperature for 38 min; After adjusting the thickness to 0.09 mm, casting was performed, and the biological membrane substrate was obtained after low-temperature drying at 41°C, cutting, and sealing packaging.

[0058] Example 8 1.2 parts of k-type carrageenan (KELCO® K-CARRA 100), 0.4 parts of l-type furcellaran (Genu Gum® I-160) and 0.1 parts of eggshell membrane powder were uniformly dispersed in 6.5 parts of glycerol, 76 parts of an aqueous dispersion medium (pure water) was added and stirred, and then 0.2 parts of Al 3+ crosslinking agent was added, the temperature was raised to 81°C for 55 min to obtain a mixed sol solution; The mixed sol solution was cooled to 51°C, 4.5 parts of antibacterial peptide was added, and defoaming was performed at constant temperature for 32 min; After adjusting the thickness to 0.14 mm, casting was performed, and the biological membrane substrate was obtained after low-temperature drying at 37°C, cutting, and sealing packaging.

[0059] Example 9 1.0 parts of k-type carrageenan (Satiagel™ UTH 18), 0.42 parts of l-type furcellaran (Alginure® I-03) and 0.11 parts of eggshell membrane powder were uniformly dispersed in 5.5 parts of glycerol, mixed and stirred with 77 parts of an aqueous dispersion medium (phosphate buffer + purified water, volume ratio 1:2, pH = 7.1), and then 0.22 parts of Ca 2+ / Al 3+ The crosslinking agents were mixed (mass ratio 3:1), and the temperature was raised to 87°C for 25 min to obtain a mixed sol solution; The mixed sol solution was cooled to 53°C, 4 parts of antibacterial peptide were added, and defoaming was performed at constant temperature for 36 min; After adjusting the thickness to 0.11 mm, casting was performed, low-temperature drying at 39°C, cutting, and sealing packaging were performed to obtain a biofilm substrate.

[0060] Example 10 1.15 parts of k-type carrageenan (Genugel® X-902-02), 0.58 parts of l-type furcellaran (GenuGum® I-160) and 0.19 parts of eggshell membrane powder were uniformly dispersed in 8.5 parts of glycerol, mixed and stirred with 68 parts of an aqueous dispersion medium (phosphate buffer, pH = 7.0), and then 0.33 parts of Al 3+ crosslinking agent was added, the temperature was raised to 89°C for 32 min to obtain a mixed sol solution; The mixed sol solution was cooled to 59°C, 2 parts of antibacterial peptide were added, and defoaming was performed at constant temperature for 48 min; After adjusting the thickness to 0.07 mm, casting was performed, low-temperature drying at 43°C, cutting, and sealing packaging were performed to obtain a biofilm substrate.

[0061] Comparative Example 1 1.0 parts of l-type furcellaran (Genu Gum® I-160) and 0.2 parts of eggshell membrane powder were uniformly dispersed in 7 parts of glycerol, mixed and stirred with 75 parts of an aqueous dispersion medium (phosphate buffer, pH = 7.0), and then 0.2 parts of Ca 2+ crosslinking agent was added, the temperature was raised to 85°C for 40 min to obtain a mixed sol solution; The subsequent steps were the same as in Example 1.

[0062] Comparative Example 2 1.0 parts of k-type carrageenan (Genugel® X-902-02) and 0.2 parts of eggshell membrane powder were uniformly dispersed in 7 parts of glycerol, mixed and stirred with 75 parts of an aqueous dispersion medium (phosphate buffer, pH = 7.0), and then 0.2 parts of Ca 2+ crosslinking agent was added, the temperature was raised to 85°C for 40 min to obtain a mixed sol solution; The subsequent steps are the same as in Example 1.

[0063] Comparative Example 3 0.8 parts of k-type carrageenan (Genugel® X-902-02), 0.3 parts of l-type furcellaran (Genu Gum® I-160) and 0.3 parts of eggshell membrane powder were uniformly dispersed in 7 parts of glycerol, mixed and stirred with 75 parts of an aqueous dispersion medium (phosphate buffer, pH = 7.0), and then 0.2 parts of Ca 2+ The crosslinking agent was added, and the temperature was raised to 85°C for 40 min of blending to obtain a mixed sol solution. The subsequent steps are the same as in Example 1.

[0064] Comparative Example 4 1.0 parts of k-type carrageenan (Genugel® X-902-02), 0.5 parts of l-type furcellaran (Genu Gum® I-160) and 0.15 parts of eggshell membrane powder were uniformly dispersed in 6 parts of glycerol, mixed and stirred with 70 parts of an aqueous dispersion medium (pure water), and then 0.3 parts of Al 3+ The crosslinking agent was added, and the temperature was raised to 80°C for 60 min of blending to obtain a mixed sol solution. The remaining steps are the same as in Example 2.

[0065] Comparative Example 5 1.0 parts of k-type carrageenan (Genugel® X-902-02), 0.5 parts of l-type furcellaran (Genu Gum® I-160) and 0.15 parts of eggshell membrane powder were uniformly dispersed in 6 parts of glycerol, mixed and stirred with 70 parts of an aqueous dispersion medium (pure water), and then 0.2 parts of glutamine transaminase crosslinking agent was added, and the temperature was raised to 80°C for 60 min of blending to obtain a mixed sol solution. The subsequent steps are the same as in Example 2.

[0066] Comparative Example 6 1.0 parts of k-type carrageenan (Genugel® X-902-02), 0.5 parts of l-type furcellaran (Genu Gum® I-160) were uniformly dispersed in 6 parts of glycerol, mixed and stirred with 70 parts of an aqueous dispersion medium (pure water), and then 0.3 parts of Al 3+ The crosslinking agent was added, and the temperature was raised to 80°C for 60 min of blending to obtain a mixed sol solution. The mixed sol solution was cooled to 50°C, 0.45 parts of an antibacterial peptide was added, and defoaming was performed at constant temperature for 30 min. After adjusting the thickness to 0.12 mm, casting was performed, and low-temperature drying at 35°C, cutting, and sealing packaging were performed to obtain a film material.

[0067] Performance test 1. Tearing resistance test Method: According to GB / T16578.1-2008 standard, the film material was cut into a rectangular sample of 100mm x 20mm, the tensile speed was set to 50mm / min, the maximum tearing force was recorded, and the tear resistance was calculated (unit: N / mm 2 ).

[0068] 2. Transdermal rate test Method: Franz diffusion cell was used to simulate the skin model, pigskin was used as the transdermal barrier, the film material was fixed between the supply chamber and the receiving chamber, the solution containing fluorescent labeled active substance was added to the supply chamber, and the receiving chamber was phosphate buffer (pH=7.4), after constant temperature stirring at 37℃ for 24h, the concentration of active substance in the receiving chamber was determined by fluorescence spectrophotometer, and the transdermal rate was calculated (unit: %, transdermal rate=total amount of active substance in receiving chamber / initial total amount in supply chamber x 100%).

[0069] 3. Swelling rate test Method: The dry film material was weighed (W0), soaked in 37℃ deionized water for 24h, and then weighed after surface water was absorbed (W1), and the swelling rate was calculated (unit: %, swelling rate=(W1-W0) / W0x100%).

[0070] 4. Biocompatibility test (skin irritation) 24h before the test, the hair on both sides of the rabbit's back spine was removed without damaging the skin, and the hair removal area was about 3cm x 3cm on both left and right sides. Take 0.5g of the test substance and apply it to one side of the skin with an area of 2.5cm x 2.5cm, carefully and slowly, without losing the sample. The other side was used as a blank control. One time a day, continuously for 14d. From the second day, the hair was cut before each application, and the residual test substance was removed with water, and 1h later, the application site was observed and recorded for the presence or absence of erythema and edema, etc., and scored according to the "skin irritation reaction score" table in the "Cosmetic Safety Technology Standard" (2015 edition), as shown in Table 1. After the test, the average integral of each animal skin reaction was calculated.

[0071] Table 1 Skin irritation reaction score

[0072] 5. Dry film wet strength Method: After the dry film was soaked in phosphate buffer (pH=7.0) for 24h, the tensile strength was tested by universal material testing machine.

[0073] The test results are shown in Table 2: Table 2 Performance test results

[0074] The tear resistance (42-50 N / mm2), transdermal rate (22-28%), swelling rate (80-100%), dry film wet strength (11-15 MPa) of the examples 1-10 all meet the core performance requirements, and the biocompatibility is non-irritating, which is due to the double seaweed gel crosslinking network of the carrageenan and red algae gel, the stable crosslinking effect of metal ions (Ca 2+ , Al 3+ ).

[0075] The comparative examples have significantly decreased performance due to material defects or process problems. The absence of necessary ingredients such as carrageenan, red algae gel, eggshell membrane powder, or the use of TG enzyme instead of metal ion crosslinking agent, the tear resistance is reduced to 18-35 N / mm 2 , the transdermal rate is lower than 15%, the swelling rate is as high as 105-400%, the dry film wet strength is reduced to a minimum of 5 MPa, and some still have slight irritation, which confirms the necessity of carrageenan, red algae gel, eggshell membrane powder, and metal ion crosslinking agent.

Claims

1. A biofilm substrate, characterized in that, The raw materials of the biofilm substrate include k-type wrinkled carrageenan, l-type red algae gum, eggshell membrane powder, glycerol and metal ion crosslinking agent; The k-type carrageenan gel strength is 800-1200 g / cm 2 Purity ≥ 90%; l-form of red algae gum has a viscosity of 300-500 mPa s, the content of G unit is 60%-85%; The mass ratio of the k-type wrinkled carrageenan, l-type red algae gum and eggshell membrane powder is 9-12:4-6:1-2.

2. The biofilm substrate of claim 1, wherein, The k-type wrinkled carrageenan includes one or more of Satiagel™ UTH 18, Genugel® X-902-02 or KELCO® K-CARRA 100; The l-type red algae gum includes one or more of Genu Gum® I-160, Alginure® I-03 or DH-I-05.

3. A method of preparing a biofilm substrate according to any one of claims 1-2, characterized in that, The method comprises the following steps: The k-type wrinkled carrageenan, l-type red algae gum and eggshell membrane powder are uniformly dispersed in glycerol, an aqueous dispersion medium is added and mixed and stirred, then a metal ion crosslinking agent is added, the temperature is raised to 80-90°C, and the mixture is blended for 20-60 min to obtain a mixed sol solution; The mixed sol solution is cooled to 50-60°C, an efficacy substance is added, and the temperature is kept constant for 30-50 min to defoam; After adjusting the thickness, casting is performed, low-temperature drying, cutting and sealing are performed, and the biofilm substrate is obtained.

4. The production method according to claim 3, characterized by, The addition amount of the aqueous dispersion medium is 65-88.6% of the total mass of the mixed sol solution.

5. The preparation method according to claim 4, characterized in that, The aqueous dispersion medium includes a phosphate buffer and / or pure water; The pH value of the phosphate buffer is 6.8-7.

2.

6. The preparation method according to claim 3, characterized in that, The metal ion crosslinking agent includes Ca 2+ and / or Al 3+ .

7. Use of a biomembrane substrate according to any one of claims 1-2 in the field of medical dressings, characterized in that, The medical dressing includes a wound dressing or a burn dressing.

8. Use of a biomembrane substrate according to any one of claims 1 to 2 in the field of cosmetics, characterized in that, The biofilm substrate is used for preparing a facial mask and / or a skin care essence carrier.

Citation Information

Patent Citations

  • Dressing containing carrageenin and preparation method thereof

    CN110227177A

  • Formulation for release rate regulating membranes for gastric resident systems

    CN114938634A

  • Coating film-forming composition

    US20210259941A1